Fostering Students’ Writing Ability by Using Facebook Comment Column - Moh Hanafi; Ayu Rizki Septiana (STKIP PGRI Tulungagung, 2021)
Teaching writing has been believed to be difficult by some experts. Some studies on writing have been made and most of them show that teachers should find appropriate techniques so that students can learn the writing skill easily. This research was focused on investigating the effectiveness of using comment column in Facebook to teach writing. The subject of this research was the second semester students of English Department in Academic Writing course. This study was a pre-experimental study in which 24 students were taken as the sample of this study. Before being given a treatment using comment column in Facebook, the students were pretested to know their initial writing ability. Then, in the end of the treatment, a posttest was administered to get the data of the students’ writing ability. To analyze the data, the researcher used Paired Sample T-test on SPSS 26.0. From the statistical analysis, it was found that the significant level was 0.000. Since it was lower than the level of significant 0.05 (0.000.05), it can be concluded that the students have significantly better writing ability after being taught using comment column in Facebook. From the findings, we can conclude that comment column in Facebook was effective to teach writing skill. Therefore, it is suggested for English teacher to use the comment column in Facebook to facilitate the students during writing class.